(untitled) (Revista Innova Educación, 2019)
The objective of this research was to determine the level of relationship between the curricular planning of teachers from the environmental focus and environmental culture in the students of the IV and V cycle of the Educational Institutions of the Upper Zone of the district of Atuncolla, Puno, period 2018. The type of research was non-experimental and its form was the descriptive and correlational, the research method was the hypothetico-deductive. The procedure for obtaining the data was through a questionnaire that was applied to teachers and students. Teachers applied the questionnaire on the processing of the environmental approach in the curricular planning in the annual programming, teaching units and learning sessions. The questionnaire was applied to the students to determine the level of the environmental culture. The results indicate that there is a positive relationship of 79. 27% on average between teacher curricular planning and the level of environmental culture.